SISTEM LEMBAGA PERWAKILAN BIKAMERAL INDONESIA - Evi Purnama Wati; Budi Aspani; Dewi Mulyati (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Bicameral is the term for a representative system consisting of two chambers (cembers) or two bodies, consisting of an upper house and a lower house in Indonesia known as the DPR RI and DPD RI which aims to achieve good governance. (good governance) as well as the achievement of checks and balances between State Institutions, especially in the Legislative Institution, which is one of the most important elements in the administration of the State. This institution has the main function in regulation, budgeting, and supervision. Although in practice this system is not perfect due to the limited role of DPD in the Political System in Indonesia. Thus, the existence of two chambers in the legislature is expected to achieve two controls in every policy issued, so that it will tend to have a positive impact on the progress of the country and in the end good governance will be achieved as the ultimate goal of a country.